3D Photonic Waveguides: High‐Resolution 3D Printed Photonic Waveguide Devices (Advanced Optical Materials 18/2020). Issue 18 (21st September 2020) - Gao, Hongwei; Chen, George F. R.; Xing, Peng; Choi, Ju Won; Low, Hong Yee; Tan, Dawn T. H.
Abstract : High‐resolution, 3D printed photonic waveguide devices are fabricated using two‐photon polymerization laser lithography (see article number 2000613 by Dawn T. H. Tan and co‐workers). Suspended waveguides with arc supports and 3D spiral waveguides are demonstrated for light guiding in three dimensions. Air‐bridge waveguide couplers with a coupling loss of 1.6 dB facilitate coupling with fibers. The fabricated waveguides are demonstrated for error‐free transmission of 30 Gb s −1 nonreturn to zero (NRZ) and 56 Gb s −1 pulse amplitude modulation (PAM‐4) high‐speed data. The results highlight interesting new capabilities enabled by 3D laser lithography that transcend the limitations of conventional lithography.